First Report of Safe Italian Peanut Production Regarding Aflatoxin - Matteo Crosta; Michele Croci; Chiara Dall’Asta; Michele Pisante; Paola Battilani (Toxins)
The growing interest in peanut production in Italy represents a significant opportunity from both an agronomic and economic standpoint. Aflatoxin B1 (AFB1) contamination is a major concern with imported peanuts; developing an Italian peanut supply chain can ensure a well-managed local product, with special care for food safety. This study aimed to provide a first overview of Italian peanut production, focusing on the Aspergillus section Flavi and AFB1 occurrence in the raw product. During 2022 and 2023, 18 peanut fields were sampled at complete maturity across the Italian production areas, considering three varieties: Lotos, SIS-AR_01, and IPG914. The results showed the occurrence of Aspergillus sec. Flavi in peanut pods, even though AFB1 was always absent or in traces, well below the European legal limits. These findings confirmed the quality of Italian peanut production, even though further research is requested to confirm the positive results of this first report.